Síntese e caracterização de híbridos PtRu/Carbono com diferentes cargas metálicas pelo método da carbonização hidrotérmica - Tusi, Marcelo Marques; Cancian, Ricardo; Polanco, Nataly Soares de Oliveira; Anaissi, Fauze Jacó; Villalba, Juan Carlo; Neto, Almir Oliveira; Spinacé, Estevam Vitorio (Ciência e Natura, 2020)
PtRu/Carbon hybrid materials with different metallic loadings (5, 10 and 20 wt%) were prepared by hydrothermal carbonization using cellulose as carbon source and reducing agent and H2PtCl6.6H2O and RuCl3.xH2O as metals sources and catalysts of the carbonization process. The as-synthesized materials were further treated under argon atmosphere at 900 oC and characterized by energy-dispersive X-ray spectroscopy (EDX), thermogravimetric analysis (TGA), X-ray diffraction (XRD), transmission electron microscope (TEM) and cyclic voltammetry (CV). The electro-oxidation of methanol was studied by chronoamperometry. The material prepared using a metallic load of 5 wt% showed the best electroactivity for methanol electrooxidation compared to others obtained materials probably due to the smaller particle size and content of oxides on surface of material.